Structural Identification, in Vitro Immunomodulatory and Antitumor Activities of Polysaccharides AHL-P from Arachis hypogaea Leaves - LU Ruijia, XIA Youlin, YOU Yu, WANG Yixue, DING Xiang, HOU Yiling (Shipin Kexue, 2023)
In this study, a polysaccharide (AHL-P) was obtained from Arachis hypogaea leaves by hot water extraction. High performance gel permeation chromatography (HPGPC), Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR), and gas chromatography mass spectrometry (GC-MS) were used to identify the structure of AHL-P. The effects of AHL-P on the proliferation of MFC cells, S180 cells, B cells (Raji), T cells (Jurkat) and RAW 264.7 cells in vitro were also tested by cell counting kit-8 (CCK-8). The results indicated that the molecular mass of AHL-P was 12.84 kDa and its monosaccharide composition consisted of glucose, xylose, galactose and arabinose at a ratio of 7:2:1:1. AHL-P was a novel polysaccharide having a backbone chain composed of (1→4, 6)-Glc, (1→4)-Xyl and (1→4)-Glc, with (1→4)-Ara and (1→4)-Gal as branches and →1)-Glc as a terminal monosaccharide of the repeating unit. The antitumor activity assay in vitro indicated that the highest inhibitory rate of AHL-P on S180 and MFC cells of 39.07% and 52.22% was observed at a concentration of 5 and 2.5 μg/mL, respectively. The immunomodulatory activity assay in vitro indicated that at 10 μg/mL AHL-P, the proliferation rate of B cells (Raji) and RAW 264.7 cells was 104.39% and 32.25%, respectively. However, AHL-P had no significantly proliferative effect on T cells (Jurkat). This study could provide a scientific basis for the development and utilization of Arachis hypogaea leaves.